The relationship between foot position in the take-off phase and the height of the jump shot in basketball - Lubinski, S.; Struzik, A. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
The purpose of this study was to identify the relationship between foot position in the take-off phase and the height of the jump shot. The research was conducted on 20 professional basketball players. Each participant performed 9 jump shots on a force plate in laboratory conditions. Jump shots were performed from three different foot positions in random order: 3 from a dominant staggered stance, 3 from a parallel stance, and 3 from a cross-dominant staggered stance. The height of the jump shots from a parallel stance (0.44 ± 0.05 m) were significantly greater than from a dominant staggered stance (0.43 ± 0.04 m) and from a cross-dominant staggered stance (0.43 ± 0.05 m). Therefore, the desirable dominant staggered stance consistent with the reference movement pattern did not prove to be more advantageous in terms of the height of the jump shot compared to other foot placements.